2006
DOI: 10.1094/cc-83-0052
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Level Protein Composition of Flour Mill Streams from a Pilot‐Scale Flour Mill and Its Relationship to Product Quality

Abstract: Flour mill streams prepared from two Australian and two New Zealand wheat cultivars using a pilot‐scale roller mill were analyzed for rheological and baking quality characteristics and for protein composition using size‐exclusion HPLC. Differences in mill stream protein composition, on an industrially relevant scale, and the relationships between the distribution of proteins (and their degree of thiol exposure) and the technological quality of the flour mill streams were examined. Consistent, significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 15 publications
11
26
0
Order By: Relevance
“…The last mill streams (B2 and R3) showed less luminosity (darker color) and higher a* (more reddish) and b* (more yellowish). This result coincided with the results of papers written by Wang and Flores (1999), Prabhasankar et al (2000), Villanueva et al (2001) and Sutton and Simmons (2006), for instance, who observed that the flour from the last streams was not as light, since they are somewhat contaminated by fragments of the aleuron layer (Greffeuille et al, 2005). The effects on the color of the crumb, both with and without improver, were the same, since the crumb does not reach 100 C and does not produce Maillard reactions or caramelization, and so its color depends largely on the color of the flour.…”
Section: Color Of Flour and Breadsupporting
confidence: 92%
See 1 more Smart Citation
“…The last mill streams (B2 and R3) showed less luminosity (darker color) and higher a* (more reddish) and b* (more yellowish). This result coincided with the results of papers written by Wang and Flores (1999), Prabhasankar et al (2000), Villanueva et al (2001) and Sutton and Simmons (2006), for instance, who observed that the flour from the last streams was not as light, since they are somewhat contaminated by fragments of the aleuron layer (Greffeuille et al, 2005). The effects on the color of the crumb, both with and without improver, were the same, since the crumb does not reach 100 C and does not produce Maillard reactions or caramelization, and so its color depends largely on the color of the flour.…”
Section: Color Of Flour and Breadsupporting
confidence: 92%
“…Nevertheless, no significant differences were observed between the last break stream (B2) and the first reduction stream (R1) in development time and stability of these parameters. These values depend more on the quality of the proteins than on the protein content (Sutton and Simmons, 2006), and in fact, a significant correlation at the 99.9% confidence level was found between flour strength, a parameter dependent on the protein quality, and stability during kneading (r ¼ 0.90).…”
Section: Resultsmentioning
confidence: 97%
“…Not unexpectedly, significant differences (P < 0.05) in protein content between the mill streams within each wheat class were detected (Table I). A similar protein distribution pattern in the break and reduction streams was reported by others (Oliver et al 1993;Sutton and Simmons 2006). 1).…”
Section: Resultssupporting
confidence: 88%
“…Ash content was correlated positively with protein content (r = 0.50, P < 0.01). Variation in parameters such as protein, ash content, damaged starch, lipids, flour color, and enzyme activity of mill streams have been reported (Rani et al 2001;Sutton and Simmons 2006). On the other hand, starch contents decreased with increasing break and reduction passages, and break streams had lower starch contents than reduction streams (Table I).…”
Section: Resultsmentioning
confidence: 91%
“…A good dough will have a balance of strength and extensibility. More fundamental rheological measurements are also being used to measure flour strength [126][127][128].…”
Section: Flour Strengthmentioning
confidence: 99%